Real‐time, non‐invasive microscopic confirmation of clinical diagnosis of bullous pemphigoid using in vivo reflectance confocal microscopy. Issue 2 (28th August 2013) - Ardigò, M.; Agozzino, M.; Amorosi, B.; Moscarella, E.; Cota, C.; de, L.; Berardesca, E.
<x xml:space="preserve">Abstract</x> Background Bullous pemphigoid is an autoimmune disease affecting prevalently the elder. In vivo reflectance confocal microscopy is a non‐invasive technique for real‐time imaging of the skin with cellular‐level resolution. No previous data has been reported about confocal microscopy of bullous pemphigoid. Aim of this preliminary study is the evaluation of the potential of in vivo reflectance confocal microscopy for real‐time, microscopical confirmation of clinical bullous pemphigoid diagnosis. Methods A total of nine lesions from patients affected by pemphigoid underwent in vivo reflectance confocal microscopy before histological examination. Results In our preliminary study, confocal microscopy showed high grade of correspondence to histopathology. In particular, presence of sub‐epidermal cleft and variable amount of oedema of the upper dermis associated with inflammatory cells infiltration were seen as prevalent confocal features in the bullous lesions considered. Differently, in urticarial lesions, no specific features could be appreciated at confocal analysis beside the presence of signs of spongiosis and perivascular inflammation. Conclusion Confocal microscopy seems to be useful for in vivo, microscopical confirmation of the clinical suspect of bullous pemphigoid and for biopsy site selection in urticarial lesions to obtain a more significant specimen for histopathological examination.